2020
DOI: 10.1177/2042018820930904
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum 25-hydroxyvitamin D levels are associated with impaired glomerular filtration rate in type 2 diabetes patients

Abstract: Background: 25-Hydroxyvitamin D [25(OH)D] deficiency has been implicated as a possible risk factor for the onset and progression of diabetes kidney disease (DKD). The aim of this study was to evaluate the interaction between levels of 25(OH)D and DKD in type 2 diabetes mellitus (DM) patients. Methods: Cross-sectional design, outpatient type 2 DM. Glomerular filtration rate (GFR) was measured by 51Cr-EDTA and estimated by Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI), urinary albumin excretion (UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…All of them support that VDD is associated with increased risk of PAD and diabetic foot ulcer formation, while the RCT concludes that VD supplementation for 12 weeks can improve wound healing. Regarding diabetic nephropathy, two studies (one cross-sectional and one retrospective study) [ 27 - 28 ] showed that VDD is associated with decreased glomerular filtration rate (GFR) and in addition VD status can be used to identify patients at increased risk of developing nephropathy complications. Although, an RCT [ 29 ] supports that VD supplementation resulted in no significant improvement of eGFR at five years.…”
Section: Reviewmentioning
confidence: 99%
“…All of them support that VDD is associated with increased risk of PAD and diabetic foot ulcer formation, while the RCT concludes that VD supplementation for 12 weeks can improve wound healing. Regarding diabetic nephropathy, two studies (one cross-sectional and one retrospective study) [ 27 - 28 ] showed that VDD is associated with decreased glomerular filtration rate (GFR) and in addition VD status can be used to identify patients at increased risk of developing nephropathy complications. Although, an RCT [ 29 ] supports that VD supplementation resulted in no significant improvement of eGFR at five years.…”
Section: Reviewmentioning
confidence: 99%
“…Circulating 25-hydroxyvitamin D levels is regarded as a sensitive determination of vitamin D status [ 27 ] and the prevalence of vitamin D insufficiency and deficiency was found to be higher in type 2 diabetic patients with chronic kidney disease and albuminuria compared to those without albuminuria [ 28 ]. In a recent study, lower 25-hydroxyvitamin D concentration was associated with reduced GFR in type 2 diabetic patients, but there was no difference between patients with elevated urinary albumin excretion compared to those with normoalbuminuria [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…After a full‐text assessment for eligibility, 141 articles were excluded. Ultimately, 23 articles were included in the meta‐analysis, 10–32 as shown in the PRISMA 33 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%